"Every day I grew stronger and stronger being there".: empowerment through land-and art-based Peer Leader retreats with Indigenous and Northern young people - Gittings, Lesley; Malama, Kalonde; Logie, Carmen H.; Lys, Candice L.; Taylor, Shira B.; Mackay, Kayley Inuksuk; Kanbari, Amanda; Parker, Samantha; McNamee, Clara (International journal of circumpolar health, 2022)
Indigenous adolescents in Canada are among those shouldering the impacts of colonialism and racism. Peer approaches and art-and-land-based programming have demonstrated promise to support empowerment and well-being, yet little is known about their efficacy with Northern and Indigenous adolescents in Canada or of how this group conceptualises empowerment. Fostering Open eXpression among Youth (FOXY) and Strength, Masculinities, and Sexual Health (SMASH) conduct land-and-arts-based Peer Leader Retreats with adolescents from the Northwest Territories, Nunavut and the Yukon Territories. Retreats (2017-2019) included 286 participants (n=196 women [trans-inclusive], n=84 men [trans-inclusive], n=5 non-binary), aged 12-19, the majority of whom (n=235) were Indigenous. Participants completed surveys immediately before and following retreats and 6 months after. Focus group discussions (FGDs) (n=24) were conducted with participants (peer leaders and apprentices) (n=232) following the retreat, and youth staff members (peer facilitators) (aged 14-21, n=7 FGDs). Applying thematic analysis, we explored retreat experiences (FGDs), and Wilcoxon signed-rank tests to examine pre/post retreat changes in leadership, empowerment, and self-confidence (surveys). Quantitatively, there were statistically significant increases in leadership and empowerment in post-retreat scores compared to pre-retreat. Qualitatively, findings demonstrate how Peer Leader Retreats premised on land-and-art-based approaches can support empowerment, confidence, leadership, and social-connectedness.